2016
DOI: 10.1177/0218492316653557
|View full text |Cite
|
Sign up to set email alerts
|

Frailty assessment to predict short term outcomes after cardiac surgery

Abstract: Frailty status impacts on both short- and intermediate-term outcomes, including postoperative quality of life. In an ageing population where nonmaleficence and resource allocation are increasingly important, individual assessment in marginal surgical candidates may provide additional information to both the patient and clinician.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…In comparison, a study of 152 cardiac surgery patients using 3 different frailty scales reported a prevalence of 20% to 46%, depending on the method chosen to define frailty 14. When 11 different frailty measures were compared in a similarly sized cardiac surgery cohort, a prevalence of 4.8% to 47% was reported 38. These diverse ranges likely reflect the diversity of frailty instruments used, the poor correlation between instruments, and the differences in the prevalence of frailty by age and surgery type.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, a study of 152 cardiac surgery patients using 3 different frailty scales reported a prevalence of 20% to 46%, depending on the method chosen to define frailty 14. When 11 different frailty measures were compared in a similarly sized cardiac surgery cohort, a prevalence of 4.8% to 47% was reported 38. These diverse ranges likely reflect the diversity of frailty instruments used, the poor correlation between instruments, and the differences in the prevalence of frailty by age and surgery type.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported on patients undergoing total aortic arch repair [ 12 ] and one study included a minority (15%) of transcatheter aortic valve replacements [ 27 ]. Pre-frail patients included those classified as “borderline,” [ 15 ] “intermediate,” [ 27 ] “moderate” [ 26 ], “middle tertile” (for 5 m gait speed) [ 14 ] and “pre-frail” [ 9 , 20 ] (Supplementary Table 1 ). The following reports were considered duplicate studies and analyzed together ([ 20 , 27 ] [ 26 , 28 , 29 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Although there is a general agreement that good early and midterm outcomes can be achieved after a cardiac operation even in older patients [22][23][24][25][26], the effect that preoperative frailty might have on the postoperative quality of life has been poorly studied [2,11,27]. In the present study, we analyzed the changes in HRQoL according to the preoperative frailty status.…”
Section: Commentmentioning
confidence: 97%